Environmental and nutritional sustainability potential of legume-based food production pathways - Saget, Sophie Tawaree (Trinity College Dublin, School of Natural Sciences, Botany, 2021)
Delivering sustainable nutrition is a key challenge for the global food sector, including in Europe, where 50% of the population is overweight, 20% obese, and where food production and consumption accounts for 30% of the continent’s greenhouse gas (GHG) emissions (Crippa et al., 2021), and is a main driver of biodiversity loss, nutrient pollution, and resource depletion (Willett et al., 2019). A substitution of locally-grown legumes for popular unhealthy products in European diets holds great potential in assisting sustainable food transformation. This PhD thesis assesses the potential delivery of nutrition at a comparatively low environmental cost of these innovative foods in a thesis-by-publication format. Comparative attributional Life Cycle Assessments (LCA) from cradle to fork or factory gate were performed between traditional foods and their legume-based alternatives. Products were compared across the sixteen impact categories recommended by the Product Environmental Footprint (PEF) guidelines (European Commission, 2018a), a breadth of environmental issues that are seldom assessed, and statistical significance assessed through Monte Carlo analyses and modified Null Hypothesis Significance Tests, a step that is rarely performed in LCA. Moreover, in addition to a mass-based functional unit (FU), a nutrient density unit (NDU) as proposed by Van Dooren (2016) was used as an additional FU for foods to capture positive nutrition in the comparison, an aspect that is often omitted in food LCAs. Primary data was collected from chickpea pasta, pea protein balls, pea-soy burger patties, and aquafaba-based (chickpea cooking water) vegan mayonnaise producers. We find that the environmental burdens of producing and consuming the legume-based foods were overall statistically significantly lower (p < 0.05) than those of the conventional foods across most categories, including a 41% average carbon footprint reduction. This advantage is further extended when using the NDU as a FU, due to the legume-based foods being on average 66% more nutrient-dense. Moreover, if consumption habits undergo minor traditional-legume substitutions, the carbon storage potential from resulting spared land represents a significant climate change mitigation opportunity. This thesis therefore highlights the potential of innovative legume-based products to deliver sustainable nutrition. Further research should focus on the environmental and nutritional effects of integrating these products at a diet level in Europe through a consequential LCA showing the effects of substituting these for their traditional alternatives, integrating full crop rotation cycles.
Keywords: Legumes; Life Cycle Assessment